Ameliorative Effect of Infused Watercress on Rat Galactopoiesis following Maternal Separation - Rahadian Yudo Hartantyo; Ucik Erlitaningsih; Jeremia Gerald; Indah Permata Sari; Laksmindra Fitria; Mulyati Mulyati (Journal of Tropical Life Science, 2018)
Galactopoiesis is the maintenance of milk production. The process that regulated primarily by prolactin hormone. The research was conducted to evaluate galactopoiesis activity by measuring prolactin level and milk production continuity of lactating rats after oral administration of infused watercress. Twenty lactating rats were randomly divided into five groups (two control groups and three variations of infused watercress dose groups). Serum prolactin was measured using enzyme-linked immunosorbent assay. Milk yield was measured using indirect milk measurement method by Sampson and Jansen. Milk protein level was measured using Kjedahl method. The treatment of infused watercress (10 g/kg body weight), started from postnatal day 3 until 12, indicated ameliorative effect on rat galactopoiesis by increasing milk yield and prolactin levels, but not milk total protein.